VHMS mineralisation at Erayinia in the Eastern Goldfields Superterrane: Geology and geochemistry of the metamorphosed King Zn deposit. Issue 2 (17th February 2019) - Hollis, S. P.; Podmore, D.; James, M.; Menuge, J. F.; Doran, A. L.; Yeats, C. J.; Wyche, S.
Abstract: Despite having been a target for volcanic-hosted massive sulfide (VHMS) deposits since the 1960s, few resources have been defined in the Archean Yilgarn Craton of Western Australia. Exploration challenges associated with regolith and deep cover exacerbate the already-difficult task of exploring for small, deformed deposits in stratigraphically complex, metamorphosed volcanic terranes. We present results of drill-core logging, petrography, whole-rock geochemistry and portable X-ray Fluorescence data from the King Zn deposit, to help refine mineralogical and geochemical halos associated with VHMS mineralisation in amphibolite-facies greenstone sequences of the Yilgarn Craton. The King Zn deposit (2.15 Mt at 3.47 wt% Zn) occurs as a 1–7 m-thick stratiform lens dominated by iron sulfides, in an overturned, metamorphosed volcanic rock-dominated sequence located ∼140 km east of Kalgoorlie. The local stratigraphy is characterised by garnet-amphibolite and strongly banded intermediate to felsic schists, with rare horizons of graphitic schist and talc schist. Massive sulfide mineralisation is characterised by stratiform pyrite–pyrrhotite–sphalerite at the contact between quartz–muscovite schists ('the footwall dacite'), and banded quartz–biotite and amphibole ± garnet schists of the stratigraphic hanging-wall. A zone of pyrite–(sphalerite) and pyrrhotite–pyrite–(chalcopyrite) veining extends throughout the stratigraphic footwall. Footwall garnet-amphibolites are of sub-alkaline basaltic affinity, with a central zone dominated by chlorite ± magnetite interpreted to represent the Cu-bearing feeder zone. SiO2, CaO, Fe2 O3T, MgO and Cu concentrations are highly variable, reflecting quartz–epidote ± chlorite ± magnetite ± sulfide alteration. Hydrothermal alteration in stratigraphically overlying intermediate to felsic rocks is characterised by a mineral assemblage of quartz–muscovite ± chlorite ± albite ± carbonate. Cordierite and anthophyllite are locally significant and indicative of zones of Mg-metasomatism prior to metamorphism. Increases in SiO2, Fe2 O3T, pathfinder elements (e.g. As, Sb, Tl), and depletions of Na2 O, CaO, Sr and MgO occur in quartz–muscovite schists approaching massive sulfide mineralisation. Within all strata (including the immediate hanging-wall), the following pathfinder elements are strongly correlated with Zn: Ag, As, Au, Bi, Cd, Eu/Eu*, Hg, In, Ni, Pb, Sb, Se and Tl. These geochemical halos resemble less metamorphosed VHMS deposits across the Yilgarn Craton and suggest that although metamorphism leads to element mobility and mineral segregation at the thin-section scale, assay samples of ∼20 cm length are sufficient to vector to mineralisation in amphibolite facies greenstone belts. Recognition of minerals such as Mg-chlorite, muscovite, cordierite, anthophyllite, biotite/phlogopite, and abundant garnet are significant, in addition to Al-rich phases (i.e. kyanite, sillimanite, andalusite and/or staurolite) not identified at King. Chemographic diagrams may be used to identify and distinguish different alteration trends, along with several alteration indices (e.g. Alteration Index, Carbonate–Chlorite–Pyrite Index, Silicification Index) and the abundance of normative corundum and quartz.